Global DNA methylation was changed by a maternal high-lipid, high-energy diet during gestation and lactation in male adult mice liver. Issue 7 (17th March 2015) - Yu, Huan-Ling; Dong, Shan; Gao, Li-Fang; Li, Li; Xi, Yuan-Di; Ma, Wei-Wei; Yuan, Lin-Hong; Xiao, Rong
Abstract : An epigenetic mechanism has been suggested to explain the effects of the maternal diet on the development of disease in offspring. The present study aimed to observe the effects of a maternal high-lipid, high-energy (HLE) diet on the DNA methylation pattern of male offspring in mice. Female C57BL/6J mice were fed an HLE diet during gestation and lactation. The genomic DNA methylations at promoter sites of genes in the liver, mRNA and protein levels of selected genes related to lipid and glucose metabolism were measured by microarray, real-time PCR and Western blot. The results indicated that the percentage of methylated DNA in offspring from dams that were fed an HLE diet was significantly higher than that from dams that were fed a chow diet, and most of these genes were hypermethylated in promoter regions. The nuclear protein content and mRNA levels of hypermethylated genes, such as PPARγ and liver X receptor α ( LXRα ), were decreased significantly in offspring in the HLE group. The results suggested that the DNA methylation profile in adult offspring livers was changed by the maternal HLE diet during gestation and lactation.